A CHARACTERIZATION OF THE U.S. RESIDENTIAL DECK MATERIAL MARKET. - SHOOK, STEVEN R. ; EASTIN, IVAN L.
CURRENT ESTIMATES INDICATE THAT OVER 6.5 MILLION DECKS ARE CONSTRUCTED ON U.S. RESIDENTIAL STRUCTURES ON AN ANNUAL BASIS AT A COST OF $1.9 TO #3 BILLION. OVER THE PAST DECADE, THE RESIDENTIAL DECK MATERIAL MARKET EXPERIENCED ROBUST EXPANSION, GROWING AT AN ANNUALIZED RATE OF 8.1 PERCENT BETWEEN 1991 AND 1999.....
Sala de Colecciones abiertas
Inglés
FORE
R2290
Keywords: MADERA; MERCADO MADERERO; Artículos de revista